Nieświadomość idioty. Myszkin i Rogożyn - Ćwik, Anna (Przegląd Rusycystyczny, 2019)
THE UNCONSCIOUSNESS OF THE IDIOT. MYSHKIN AND ROGOZHIN Summary The aim of the article is to present Fyodor Dostoevsky’s The Idiot psychoanalytic analysis, focusing on the main characters of the novel. One idea is common for many interpretations, mainly the thought that Prince Myshkin and Rogozhin represent the duality of human nature. In this work the author makes an attempt to determine the exact configuration in which literary figures exist, taking into consideration Sigmund Freud’s legacy, as well as some concepts of analytical psychology as developed by Carl Gustav Jung. Through the application of the structural model of the psyche, Jungian archetypes, and both the idea of personal and collective unconscious we find that Myshkin and Rogozhin may be seen as superego and id, whereas Nastasya Filipovna symbolises ego that is torn between them. As they fail to conform to the demands of reality, they also illustrate the philosophical theme in the novel.